2013
DOI: 10.1155/2013/383278
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between Antimullerian Hormone and Follicle Stimulating Hormone in Assisted Reproduction

Abstract: Data from 107 women undergoing their first IVF/ICSI were analyzed. Relationships between antimullerian hormone (AMH) and follicle stimulating hormone (FSH) were analyzed after dividing patients into four groups according to AMH/FSH levels. Concordance was noted in 57% of women (both AMH/FSH either normal or abnormal) while 43%of women had discordant values (AMH/FSH one hormone normal and the other abnormal). Group 1 (AMH and FSH in normal range) and group 2 (normal AMH and high FSH) were younger compared to gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
0
15
0
2
Order By: Relevance
“…The importance of AMH in human reproduction is confirmed by research of Hussain et al, Lehmann et al, Reichmanm et al, and Wdowiak et al, which indicate that the chance for achieving pregnancy grows together with an increase in the level of AMH in the case of treatment by the in vitro fertilization method. The abovementioned studies did not unequivocally show whether FSH or AMH has a greater predictive value in achieving pregnancy [ 10 , 27 , 28 , 29 ]. In this study, women with very high AMH (polycystic ovarian syndrome) and those with lowered levels of this hormone (premature menopause) were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of AMH in human reproduction is confirmed by research of Hussain et al, Lehmann et al, Reichmanm et al, and Wdowiak et al, which indicate that the chance for achieving pregnancy grows together with an increase in the level of AMH in the case of treatment by the in vitro fertilization method. The abovementioned studies did not unequivocally show whether FSH or AMH has a greater predictive value in achieving pregnancy [ 10 , 27 , 28 , 29 ]. In this study, women with very high AMH (polycystic ovarian syndrome) and those with lowered levels of this hormone (premature menopause) were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective study on women undergoing their first IVF/ICSI cycle, however, concordance between AMH and FSH was noted in 57% of women while 43% of women had discordant values. According to these results, authors concluded that both AMH and FSH tests are probably useful to predict ovarian response but since many women have discordant values, it is difficult to counsel patients regarding their true ovarian reserve using one single marker [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that women with a single ovary had higher basal follicle stimulating hormone (FSH) when compared with patients with both ovaries, and it was confirmed that higher FSH is an indicator of poor response for IVF protocols. 15 Unfortunately, we could not compare the age range of our patients, but we observed that patients who had their ovariectomy younger in life responded well. There is no comparative data available to confirm the dominance of one ovary over the other, or which is more important for conception.…”
Section: Discussionmentioning
confidence: 85%